Luspatercept as a therapy for myelodysplastic syndromes with ring sideroblasts. Issue 6 (3rd June 2021) - Schulz, Felicitas; Nachtkamp, Kathrin; Kasprzak, Annika; Gattermann, Norbert; Haas, Rainer; Germing, Ulrich
ABSTRACT: Introduction: Myelodysplastic syndromes (MDS) are a heterogeneous group of hematopoietic stem cell diseases characterized by cell dysplasia, ineffective hematopoiesis and risk of transformation to acute myeloid leukemia (AML). The median age of 75 years at diagnosis is associated with the presence of comorbidities, which preclude intensive therapies like allogeneic hematopoietic stem cell transplantation in most MDS patients. Risk stratification using the (Revised) International Prognostic Scoring System (IPSS/IPSS-R) is necessary to plan individualized treatment. Areas covered: Luspatercept (ACE-536), a speciﬁc activin receptor fusion protein, promotes late-stage erythropoiesis. Two clinical trials, PACE-MDS (phase 2) and MEDALIST (phase 3), yielded positive results in terms of improved hemoglobin levels and loss of transfusion dependence, with hardly any side effects. A phase 3 trial to compare luspatercept to ESAs (COMMANDS study) is ongoing. Expert opinion: Luspatercept is a promising alternative to ESAs for a subset of transfusion-dependent patients with lower risk MDS, namely those with a sideroblastic phenotype who are either not suitable for or have already failed erythropoietin-based treatment. The favorable safety profile and convenient subcutaneous administration every 3 weeks are more conducive to patients' quality of life than chronic red blood cell transfusion therapy.